INVENTARISASI PARASIT PADA IKAN HIAS BOTIA (Botia macracanthus) DI SUNGAI KELEKAR, KABUPATEN OGAN ILIR, PROVINSI SUMATERA SELATAN - ROBIN ROBIN (Akuatik: Jurnal Sumberdaya Perairan, 2007)
Many types of ornamental freshwater fish are economically important commodity for national and international trade. The quality and value of ornamental botia fish is dice to their performance. Performance and productivity of ornamental fish can be destroyed and decreased by parasite infection. The aim of this current research is to inventory the parasite types and their specific attack area on ornamental botia fish (Botia Macracanthus) in Kelekar River, District of Ogan Ilir, South Sumatra Province. This research was done from 1 to 30 August 2005. The fish samples were collected from Kelekar River. Fish observation was done at Biology laboratory, Faculty of Teaching and Education, Sriwijaya University. Before fishes were observed, fish body weight and length were determined, inspection of Botia fish including cover part, mucus, gill, eye, stomach cavity, digestive channel and tendon. All parasites found were made wet and permanent preparat for detailed parasite observation. Data collected in this current research are parasite type, prevalent area and intensity of parasite infection. Data were intended then analyzed descriptively. Fish samples are infected by parasites consist of Ichthypphthirius multiflliis, Ambloplifis Achtheres, Argulus Indicus and Glochidia, which represent ectoparasite. Specific areas attacked by Ichthyophthblus multifiliis and Argulus indicus are fin, husk and gill. Specific area attacked by. Ambloplitis Achtheres and Glochidia is gill. Specific host of Ichthyophthirius Multifiliis is ornamental Botia fish (Botia Macrachanthus). Endoparasite consists of Gordius sp and Proteocephalus parallacticus which attacked digestive fish organ. The prevalent and attacking intensity of Ichthypphthirius Multifiliis on ornamental fish body of Botia (Botia Macracanthus) are 100% and 153, 33, inspectively